Do Adults with High Functioning Autism or Asperger Syndrome Differ in Empathy and Emotion Recognition? - Montgomery, Charlotte B. (J Autism Dev Disord, 2016)
The present study examined whether adults with high functioning autism (HFA) showed greater difficulties in (1) their self-reported ability to empathise with others and/or (2) their ability to read mental states in others’ eyes than adults with Asperger syndrome (AS). The Empathy Quotient (EQ) and ‘Reading the Mind in the Eyes’ Test (Eyes Test) were compared in 43 adults with AS and 43 adults with HFA. No significant difference was observed on EQ score between groups, while adults with AS performed significantly better on the Eyes Test than those with HFA. This suggests that adults with HFA may need more support, particularly in mentalizing and complex emotion recognition, and raises questions about the existence of subgroups within autism spectrum conditions.